2014
DOI: 10.1111/iwj.12309
|View full text |Cite
|
Sign up to set email alerts
|

A non‐randomised, controlled clinical trial of an innovative device for negative pressure wound therapy of pressure ulcers in traumatic paraplegia patients

Abstract: The conventional methods of treatment of pressure ulcers (PUs) by serial debridement and daily dressings require prolonged hospitalisation, associated with considerable morbidity. There is, however, recent evidence to suggest that negative pressure wound therapy (NPWT) accelerates healing. The commercial devices for NPWT are costly, cumbersome, and electricity dependent. We compared PU wound healing in traumatic paraplegia patients by conventional dressing and by an innovative negative pressure device (NPD). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Except in a sub-set of PUs, the authors did not find any statistically significant differences in the time to closure between the two treatment groups. They found a significant difference in time to closure of PU (mean 10±7.11 days) between the treatment and control groups (27±10.6 days, p=0.05) [1,2,4]. In our study, the reduction in surface area and depth of PUs treated by our NPD was faster than the PUs treated by standard wound care.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…Except in a sub-set of PUs, the authors did not find any statistically significant differences in the time to closure between the two treatment groups. They found a significant difference in time to closure of PU (mean 10±7.11 days) between the treatment and control groups (27±10.6 days, p=0.05) [1,2,4]. In our study, the reduction in surface area and depth of PUs treated by our NPD was faster than the PUs treated by standard wound care.…”
Section: Discussionmentioning
confidence: 45%
“…PUs are complex and chronic wounds in patients with SCI and no gold standard has yet been established for their prevention and treatment. PUs are difficult to prevent and manage and can lead to a decline in the overall well-being of patients in SCI [2,4,5,16]. In this study, the novel NPD proposed by us showed a statistically significant improvement in PU healing in terms of reduction in the surface area and depth, slough clearance, granulation tissue formation, and removal of exudate as compared with standard wound care.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A nonrandomized controlled trial comparing NPWT to conventional dressings showed a significant reduction in wound size with NPWT. 30 Another RCT that compared NPWT to modern dressings reported a reduction in the mean ulcer volume from 42% in controls to 52% for NPWT, not statistically significant ( p = 0.46). 31 Finally, a pro- Figure 1.…”
Section: Npwt-pressure Ulcermentioning
confidence: 96%